Li@C60 as a multi-state molecular switch - Henry J. Chandler (Nature Portfolio, 2019)
Molecular switches that can access more than just a few states are difficult to realize. Here, the authors use scanning tunnelling microscopy and spectroscopy to show that a surface-bound Li@C60 endofullerene can be switched between 14 molecular states—distinguished by the location of the Li atom inside the fullerene cage—by resonant tunnelling through the superatom molecular orbitals.